2003
DOI: 10.1007/s00066-003-1086-0
|View full text |Cite
|
Sign up to set email alerts
|

Wo stehen wir bei der Behandlung des Nasopharynxkarzinoms?

Abstract: It will be necessary to treat patients with different histologic subtypes with an uniform treatment schedule to define the place of combined modality treatment. This will probably be the only way to develop treatment concepts for distinct stages and biological entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
2
0
2
Order By: Relevance
“…The rate of severe late radiation complications was also low (3%). In other studies this rate was reported in the range of 0-10% [1,18,21,32,35]. It is also to be noted, that 2/10 (20%) patients with local failure were successfully salvaged and cured, yielding an ultimate crude local tumor control of 73% (22/30).…”
Section: Discussionmentioning
confidence: 88%
“…The rate of severe late radiation complications was also low (3%). In other studies this rate was reported in the range of 0-10% [1,18,21,32,35]. It is also to be noted, that 2/10 (20%) patients with local failure were successfully salvaged and cured, yielding an ultimate crude local tumor control of 73% (22/30).…”
Section: Discussionmentioning
confidence: 88%
“…More rigorous treatment strategies are clearly needed for advanced tumors. Numerous authors report a better target/normal tissue dose distribution using intensity-modulated radiation therapy (IMRT), stereotactic irradiation (SRT), or two-step intensity-modulated arch therapy (two-step IMAT) [4,5,16,20,24,41,47,58,64,70]. These modalities can allow for optimization of the dose distribution and administration of higher cumulative irradiation doses (e.g., 81 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…Die perkutane Strahlentherapie ist ein zentraler Bestandteil in der Behandlung eines Nasenrachenkarzinoms, die insbesondere bei lymphknotenpositiven Tumoren in aller Regel um eine simultane Chemotherapie ergänzt wird [4]. Als weitere strahlentherapeutische Behandlungsoption steht sowohl im Rahmen des primären Behandlungskonzepts als auch bei Rezidiven eine Brachytherapie zur Verfügung.…”
Section: Diskussionunclassified
“…Zur Behandlung von Karzinomen im Bereich des Nasenrachens kommen verschiedene Therapiekonzepte zur Anwendung, die das Bedürfnis nach verbesserten Therapiekonzepten in Anbetracht unbefriedigender Ergebnisse unterstreichen [4]. So sind nach kombinierter chirurgischer Resektion und perkutaner Strahlentherapie bzw.…”
Section: Introductionunclassified